I sense that there is someone else: an exploratory study on the influence of the media richness of Augmented Reality-based assistance systems on team experience and performance - Thomaschewski, Lisa; Feld, Nico; Weyers, Benjamin; Kluge, Annette (Frontiers in Virtual Reality, 2023)
Based on the results of two laboratory studies, we show how the implementation of minimalistic social and task-relevant cues in Augmented Reality-based assistance systems for spatially dispersed teams impact team experience while not affecting team performance. In study 1 (N = 224) we investigated the Ambient Awareness Tool, which supports spatially dispersed teams in their temporal coordination when multiple team tasks or team and individual tasks must be executed in parallel. We found that adding a progress bar to the interface led to a significant increase in the perception of work group cohesiveness (diff = 0.34, p = .03, CI: [−0.65; −0.03], d = 0.39), but did not affect team performance (p = .92, η² = 0.03). In study 2 (N = 23) we piloted an AR-based avatar representation of a spatially dispersed team member and evaluated whether the interactivity of the avatar impacts the perception of co- and social presence as well as team performance. An interactive avatar increased the perception of co- and social presence (co-presence: diff = 2.7, p < .001, η² = 0.20; social presence: diff = 1.2, p = .001, η² = 0.06). Team performance did not differ significantly (p = .177, η² = 0.01). These results indicate that even minor social and task-relevant cues in the interface can significantly impact team experience and provide valuable insights for designing human-centered health-promoting AR-based assistance systems for spatially dispersed teams in the vocational context with minimal means.